Purification, biochemical, and thermal properties of fibrinolytic enzyme secreted by Bacillus cereus SRM-001. Issue 1 (2nd January 2018) - Narasimhan, Manoj Kumar; Ethiraj, Selvarajan; Krishnamurthi, Tamilarasan; Rajesh, Mathur
ABSTRACT: The discovery of microbial fibrinolytic enzymes is essential to treat cardiovascular diseases. This study reports the discovery of a fibrinolytic enzyme secreted by Bacillus cereus SRM-001, a microorganism isolated from the soil of a chicken waste-dump yard. The B. cereus SRM-001 was cultured and the secreted fibrinolytic enzyme purified to show that it is a ∼28 kDa protein. The purified enzyme was characterized for its kinetics, biochemical and thermal properties to show that it possesses properties similar to plasmin. A HPLC-MS/MS analysis of trypsin digested protein indicated that the fibrinolytic enzyme shared close sequence homology with serine proteases reported for other Bacillus sp . The results show that the B. cereus SRM-001 secreted enzyme is a ∼28 kDa serine protease that possesses fibrinolytic potential.